A cross‐sectional study of COVID‐19 vaccination patterns among patients with epilepsy in Hong Kong. Issue 4 (24th August 2022) - Chan, Charlie CH; Choi, Chun‐Ho; Lui, Wai Ting; Ip, Bonaventure; Ma, Karen KY; Ma, Sze Ho; Fan, Florence SY; Au, Lisa; Lau, Alexander; Chan, Anne YY; Ip, Vincent; Soo, Yannie; et al.
Abstract: Objective: As Hong Kong faced the 5th wave of the COVID‐19 pandemic, the facilitators and hurdles toward effective vaccination is important for healthcare professionals to understand the vaccination gap among patients with epilepsy. Methods: A cross‐sectional, pragmatic study of COVID‐19 vaccination was performed at a tertiary epilepsy center with regards to patterns of vaccination and any unusually high rate of adverse events. Patients having recent visits at the epilepsy center (4 months) had their anonymized electronic linkage records examined 12 months after the inception of vaccination program for types of vaccines, seizure demographics, and adverse events following immunization (AEFI). Results: A total of 200 patients with epilepsy and their anonymized data were analyzed. The vaccine uptake was approximately 60% of that of the general population. Twice as many patients with epilepsy chose to receive mRNA vaccine as compared with inactivated vaccine. The proportion of patients who kept up‐to‐date with all available dosing was 7%. Patients with epilepsy with genetic etiology were least likely to receive vaccination (13/38, 34%, P = .02). There was no unreasonably high rate of unacceptable side effects after vaccination among patients with epilepsy. Only 3 patients reported worsening of seizures without meeting the criteria for AEFI. Refractory epilepsy, allergy to antiseizure medications and elder age (≥65) did not confer any significant difference in vaccination patterns or adverse effects. Significance: A vaccination gap exists among epilepsy patients which calls for actionable strategies for improving vaccine uptake, including education and outreach programs.